تأثير الإجهاد الملحي على إنبات و نمو الذرة - مدخل, خدیجة; عازب عثمان, زھیرة; مؤمن مسعود, مبروكة; حمیداتو, نسیبة (جامعة الوادي - University of Eloued, 2014)
The research aimed to study the efect of the salt stres irigation on the Corn plant a physiologicaly and the morphology states during both phases of germination and growth development by aplying the salt stres experimentaly using NaCl salt solution or saline naturaly water. Was found that the salt stres have a significant impact on the Corn plant where reduces the rate and the sped germination. Has ben shown by the results that the Corn plant may asumes low-and midle grades of salt stres does not asume high levels of salinity.
بيولوجيا و فيزيولوجيا النبات
Keywords: Corn , Germination , Growth , saline stres.; الذرة الشامیة ، الإنبات ، النمو ، الإجھاد الملحي